Mobile genetics and forms of heritable changes in eukaryotes - Golubovsky, M. (Биополимеры и клетка, 1995)
The real insight in the eukaryotic genome means knowledge of the structure of genetic elements, the character of dynamic links between them and some holistic features of the system. The structure of the eukaryotic genome can be naturally subdivided on two classes of elements: an obligatory and facultative ones. Accordingly, we need to discriminate between two different forms of heritable changes – mutations and variations. Mutations correspond to all changes with genes. Variations are various kinds of changes in the populations of genomic facultative elements. Variations may be directed and connected with multiple site specific alterations. The spontaneous mutation process in nature is mediated by the system of facultative elements. Their activation in nature induces sudden mutation outbursts, appearance of new genetic constructions and site specific rearrangements. Facultative elements are the first to react on environmental challenge. Variations can be presented as an operational memory of the genome. Between obligatory and facultative elements there is constant flow. The behavior of transposons in the eukaryotic genome may be model for the adequate description of epigenic inheritance. There is logic and real necessity to use the epigene concept for describing of elementary units of epigenetic inheritance.